Perspective: Assessing the Flexible Acquisition, Integration, and Deployment of Human Spatial Representations and Information - Starrett, Michael J.; Ekstrom, Arne D. (Frontiers in Human Neuroscience, 2018)
Studying human spatial navigation in the lab can be challenging, particularly when including non-invasive neural measures like functional magnetic resonance imaging (fMRI) and scalp encephalography (EEG). While there is broad consensus that human spatial navigation involves both egocentric (self-referenced) and allocentric (world-referenced) coding schemes, exactly how these can be measured in ecologically meaningful situations remains controversial. Here, we explore these two forms of representation and how we might better measure them by reviewing commonly used spatial memory tasks and proposing a new task: the relative vector discrimination (RVD) task. Additionally, we explore how different encoding modalities (desktop virtual reality, immersive virtual reality, maps, and real-world navigation) might alter how egocentric and allocentric representations manifest. Specifically, we discuss desktop virtual reality vs. more immersive forms of navigation that better approximate real-world situations, and the extent to which less immersive encoding modalities alter neural and cognitive codes engaged during navigation more generally. We conclude that while encoding modality likely alters navigation-related codes to some degree, including egocentric and allocentric representations, it does not fundamentally change the underlying representations. Considering these arguments together, we suggest that tools to study human navigation in the lab, such as desktop virtual reality, provide overall a reasonable approximation of in vivo navigation, with some caveats.